Analysis Of The Effect Of Satisfaction And Workload On Employee Performance At Samsung Store Sun Plaza Medan - Ruth Lily Angioline Siahaan; Ahmad Aswan Waruwu (Penerbit Jurnal Indonesia, 2025)
Various factors can affect employee performance in an organization, including job satisfaction and workload. In the electronics industry, where direct interaction with customers is a key aspect, the balance between employee satisfaction and workload plays a significant role in determining productivity and service quality. Samsung Store Sun Plaza Medan is an official Samsung outlet that offers various Samsung electronic products and after-sales services to consumers, not free from the challenge of maintaining and improving employee productivity. This study uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to all employees of Samsung Store Sun Plaza Medan as respondents. The population in this study was 44 employees of Samsung Store Sun Plaza Medan. The sampling technique was a saturated sample so that the number of samples was 44 respondents. The independent variables in this study were job satisfaction and workload, while the dependent variable was employee performance. The data analysis technique used was multiple linear regression to determine how much influence the two independent variables had on employee performance and was processed using SPSS software version 29.0. The results of the study indicate that partially, job satisfaction has a significant effect on employee performance with a t-count value (3.496) > t-table (2.01808) and a significance of 0.001 < 0.05. While workload does not have a significant effect on employee performance with a t-count value (0.091) < t-table (2.638) and a significance of 0.928 > 0.05. Simultaneously, job satisfaction and workload have a significant effect on employee performance with an F-count value of 14.047 > F-table 3.22 and a significance of 0.001 < 0.05. The R Square value of 0.638 indicates that job satisfaction and workload affect employee performance by 63.8%, while the remaining 36.2% is influenced by other factors not examined in this study.